An evaluation of the in-service education of public elementary school mathematics teachers in the Division of Cagayan I (1967-1972) - Gayagoy, Concepcion Singson 1935- (1975)
Inservice training in modern mathematics instruction was appraised by 360 public elementary mathematics teachers through a questionnaire. Interviews with 15 school heads and 8 district mathematics coordinators and observations of mathematics classrooms in the 15 districts supplemented questionnaire information. Analysis of percentages, mean values and rank order reavealed that trained demonstration teachers and resource persons enriched the teachers' content background and promoted the use of the discovery approach. The training program was planned in a "desirable" manner and achieved its objectives adequately except in the areas of test construction and interpretation and in the use of Peace Corps services.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers -- In-service training -- Philippines; Mathematics teachers